Analysis of pharmaceutical products and dietary supplements seized from the black market among bodybuilders. (May 2021) - Fabresse, Nicolas; Gheddar, Laurie; Kintz, Pascal; Knapp, Adeline; Larabi, Islam Amine; Alvarez, Jean-Claude
Highlights: First analysis of pharmaceuticals and AAS bought on internet in France. 33% of pharmaceuticals were substandard. 32% of pharmaceuticals were counterfeit. 80% of AAS were non original. 3% of dietary supplement was adulterated. Abstract: Substandard/counterfeit drugs are a growing global problem. According to the World Health Organisation, counterfeit medicines are medicines that are mislabelled deliberately and fraudulently regarding their identity and/or source. In high income countries, drugs seized are mainly represented by performance and image enhancing drugs (PIEDs). The aim of this study was to present the qualitative and quantitative results of toxicological analyses of pharmaceutical and dietary supplements seized from the black market among bodybuilders in France. All dietary supplements and pharmaceuticals seized from the black market and addressed to the laboratory for a qualitative and quantitative analysis between January 2016 and December 2019 were included in the study. A screening was carried out by gas chromatography-mass spectrometry and liquid chromatography-high resolution mass spectrometry. Identified compounds were quantified by liquid chromatography-tandem mass spectrometry. One hundred and ten products were seized and submitted to the laboratory for identification of active compounds and quantification: 75 pharmaceuticals and 35 dietary supplements. This included 39 oily and 3 aqueous solutions for intramuscular injection, 34 tablets, 13 capsules, 14 powders, 4 liquids and 3 lyophilizates. Among the pharmaceuticals, 25/75 (33%) were substandard (dosage not on the acceptable range defined for original products), 24/75 (32%) were counterfeit (qualitative formulation does not match the label) and 14/75 (19%) were original (qualitative formulation and levels of active ingredients fully matches the declared formulation. The analysis of the 12 remaining products revealed a correct qualitative content for 11/75 (15%), but quantitation could not be carried out because of the lack of reference standards at the time of the analysis. Fifty-four pharmaceuticals contained anabolic-androgenic steroids (AAS). Four out of 54 (7.4%) AAS were found as original, 8/54 (15%) could not be quantified (one with wrong active ingredient), corresponding to 43/54 (80%) AAS being non-original. In contrast, only 1/35 dietary supplement (3%) was adulterated, with a doping substance (1, 3-dimethylbutylamine, DMBA). This work allows to show that France is not spared by the trafficking of PIEDs. The use of counterfeit drugs in mainstream population is an underestimated public health issue.